To what extent do paramedics apply safe handling principles when transferring patients from stair chairs to stretchers?. Issue 10 (3rd October 2019) - Larouche, Dominique; Corbeil, Philippe; Bellemare, Marie; Authier, Marie; Prairie, Jérôme; Hegg-Deloye, Sandrine
Abstract: The efficiency of training programmes in handling designed to prevent injuries has rarely been demonstrated by studies in the workplace. This study aimed to identify factors that may favour or inhibit the application of safe handling principles by paramedics performing full-body transfers of patients from a stair chair to a stretcher. In an observational field study, handling methods used in 45 patient transfers from a stair chair to stretcher were characterised. Principles concerning the physical environment seem to be applied frequently, but those applicable during the transfer are neglected. Principles taught during training may not be applied due to the physical constraints of the workplace and the underestimation of risk exposure. The results suggest that training should be enhanced, not by focussing on handling techniques but by focussing on compromise and the capacity to adapt work techniques based on the working context and the team-mate. Practitioner Summary: To assess safe handling principles applied by paramedics transferring patients from stair chairs to stretchers, an observational field study and a posteriori analysis were conducted. The results suggest that training should focus more on the ability to adapt work techniques according to the work context and the team-mate. Abbreviations: MSDs: musculoskeletal disorders; IRSST: Institut de recherche Robert-Sauvé en santé et en sécurité du travail